Mousekin's Thanksgiving - Miller, Edna, 1920- (Englewood Cliffs, N.J. : Prentice-Hall, 1985)
Mousekin and his forest friends struggle to survive the winter together with a wild turkey.
Children's Catalog (Wilson)
School Library Journal
Bulletin Of The Center For Children's Books
3.1
K-3
Keywords: Mice -- Juvenile fiction; Mice -- Fiction; Turkeys -- Fiction; Winter -- Fiction; Mice -- Fiction; Turkeys -- Fiction; Winter -- Fiction